Pengaruh Hedonic Shopping Motivation dan Shopping Lifestyle terhadap Impulse Buying pada Konsumen E-Commerce Shopee Surabaya - Sofiyah Salsabilah; Iswati Iswati; Arief Widjadmoko (JURNAL RISET MANAJEMEN (JURMA), 2024)
The purpose of this study is to determine and analyze the effect of hedonic shopping motivation on impulse buying, to determine and analyze the effect of shopping lifestyle on impulse buying and to determine and analyze the effect of hedonic shopping motivation and shopping lifestyle on impulse buying for Shopee e-commerce consumers. The population in this study were Shopee consumers in the Surabaya area, with a sample size of 100 respondents with a Purposive sampling technique, the data collection method used was the questionnaire method with Google Form. Data analysis used in this study was validation testing, reliability testing, classical assumption testing, multiple linear regression, hypothesis testing and coefficient of determination. The results showed that there was a positive and significant effect of the hedonic shopping motivation variable on impulse buying, there was a positive and significant effect of the Shopping lifestyle variable on impulse buying and testing carried out simultaneously showed that there was a significant relationship and influence between the hedonic shopping motivation and Shopping lifestyle variables on impulse buying for Shopee e-commerce consumers in Surabaya.